Healing violent men : a model for Christian communities - Livingston, David J. (Minneapolis, MN : Fortress Press, 2002)
Violent men in our communities : the dynamics of intimate violence -- Violence : destruction of the mysterious human center -- Does Christianity throw gas on the flames of violence? -- Reconciliation : a model for addressing male violence -- Reconciliation : a responsible approach to intimate violence.
Includes bibliographical references (p. 121-126) and index.
Keywords: Family violence -- Religious aspects -- Christianity; Wife abuse -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity